1999
DOI: 10.1046/j.1365-2222.1999.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of specific immunotherapy with house dust mite extract on the bronchial responsiveness of paediatric asthma patients

Abstract: These results demonstrate that during 2 years of SIT there was a reduction of bronchial hyperresponsiveness in HDM-allergic paediatric asthma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 30 publications
2
15
0
1
Order By: Relevance
“…Allergen-specific immunotherapy has the potential to modify the natural course of allergic diseases [35, 27, 28]. Many different in vivo and in vitro tests have been used to determine the efficiency; however, predictive tests for the clinical response to SIT are limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allergen-specific immunotherapy has the potential to modify the natural course of allergic diseases [35, 27, 28]. Many different in vivo and in vitro tests have been used to determine the efficiency; however, predictive tests for the clinical response to SIT are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several successful immunotherapy studies have shown an induction of peripheral tolerance and an anergic state in activated specific T cells [1012, 27, 28]. On the other hand, a significant decrease in skin prick test reactivity can be also observed relatively late in the course [35]. Therefore, many clinicians want to find out objective and easily performed parameters to predict the efficacy of SIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicht-pharmakologische Provokationsmethoden, wie z. SIT-Jahr fortgesetzt [23]. Eigene Untersuchungsergebnisse nach 1jä hriger SIT mit einem Aluminiumhydroxid-adsorbierten Hausstaubmilbenextrakt zeigten eine Abnahme der mit Kaltlufthyperventilationsprovokation gemessenen BR, jedoch keinen statistisch signifikanten Un-terschied zur Kontrollgruppe; diese Untersuchung wird z.…”
Section: Bronchiale Applikationunclassified
“…Bousquet et al [6] Carbachol FEV1 (PD20) < 0,005 Delta FEV1 < 0,04 Formgren et al [18] Histamin FEV1 (PC20) ns Garcia-Ortega et al [21] Methacholin FEV1 (PD20) ns Gruber et al [23] Kaltluft Delta FEV1 < 0,05 ns Mosbech et al [33] Histamin FEV1 (PC20) a ns ns FEV1 (PC20) b ns ns Haugaard et al [24] Histamin FEV1 (PC20) c < 0,01 ns FEV1 (PC20) d < 0,01 ns FEV1 (PC20) e < 0,01 ns Van Bever u. Stevens [57] Histamin FEV1 (PD20) ns ns…”
Section: Subkutane Applikationmentioning
confidence: 99%